Turkish IBD Organization’s Position Statement on Inflammatory Bowel Disease Management Recommendations During COVID-19 Pandemic - Törüner, Murat; Kalkan, İsmail Hakkı and Akyüz, Filiz and Tezel, Ahmet and Çelik, Aykut Ferhat (Turkish Journal of Gastroenterology, 2021)
The COVID-19 pandemic, caused by the novel severe acute respiratory syndrome coronavirus 2, has resulted in high mortality and morbidity worldwide and is still a growing problem. Inflammatory bowel disease (IBD) is a chronic inflammatory disease for which a substantial number of patients are treated with immunosuppressive medications, either occasionally or long-term. Despite the accumulating evidence, there is still a lack of knowledge about the impact of COVID-19 on IBD patients, especially those who are under immunosuppressive treatment. Moreover, following the emergence of several COVID vaccines, there are concerns regarding vaccine effectiveness and possible side effects in such patients. In this context, we tried to briefly summarize the accumulating evidence and recommendations for the management of IBD in the context of the COVID-19 pandemic.